The effect of various classes of glucose-lowering medications on the blood vessel elasticity in patients with type 2 diabetes - S. V. Nedogoda; I. N. Barykina; A. S. Salasyuk; T. N. Sanina; V. O. Smirnova; E. A. Popova (Российский кардиологический журнал, 2020)
Aim. To study the effect of various classes of glucose-lowering agents (dipeptidyl peptidase-4 (DPP-4) and sodium-glucose cotransporter-2 (SGLT-2) inhibitors) on the vascular stiffness in patients with type 2 diabetes (T2D) and high cardiovascular risk.Material and methods. The open-label, prospective 24-week study included 120 patients with T2D and high cardiovascular risk. We evaluated the effect of modern glucose-lowering medications, empagliflozin at a dose of 25 mg/day (SGLT-2 inhibitor) and sitagliptin at a dose of 100 mg/day (DPP-4 inhibitor), on vascular elasticity, central hemodynamic and laboratory parameters.Results. After 24-week therapy, the target glycated hemoglobin level reached 71% and 80% of patients in the sitagliptin and empagliflozin groups, respectively. In both groups, vascular stiffness and central hemodynamic parameters were improved. However, significant changes were recorded only in the empagliflozin (carotid-femoral pulse wave velocity decreased by 14,4%, augmentation index — by 6%, central pulse pressure — by 7,8%) (p<0,05). Use of sitagliptin was associated with significant improvements in the lipid profile (total cholesterol decreased by 9,5%, triglycerides — by 21%, low density lipoproteins — by 15,1%; high density lipoproteins increased by 15,7%) (p<0,05). In the empagliflozin group, anthropometric parameters were improved (body mass index decreased by 9,1%, waist circumference — by 4,1%) (p<0,05). Patients in both groups had a significant decrease in HOMA-IR index and highly sensitive C-reactive protein: by 34% and 51,6% in the empagliflozin group and by 31,8% and 22,1% in the sitagliptin group, respectively (p<0,05).Conclusion. The use of empagliflozin is more associated with arterial stiffness decrease in T2D patients with high cardiovascular risk compared with sitagliptin.